Implementasi Peraturan Zakat Terhadap Konsep Amil di Masjid Medan Utara - Ingah Maulana; Sukiati Sukiati; Syafruddin Syam (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2021)
This study aims to understand and analyze: 1. The understanding of the administrators of the Mosque Prosperity Agency in North Medan regarding the concept of amil zakat, 2. The extent to which zakat regulations regarding amil zakat are implemented in North Medan mosques, and 3. What factors influence the implementation of zakat regulations. on the concept of amil in the North Medan mosque. The type of research that the researcher conducts is empirical research with a sociological legal approach, and the nature of this research is qualitative-descriptive-inductive. The subject of this research is the mosque community or BKM in North Medan. Primary data were obtained by researchers through interviews, as well as questionnaires (questionnaires) that researchers gave to 46 (forty six) BKMs in all urban villages in North Medan. The results of the study show that: 1. The majority of BKM in Majid Medan Utara in the period before 2020 understood that KUA was the institution authorized to raise zakat amil at the North Medan mosque (81% of all respondents). The factors that influence the implementation of zakat regulations on the concept of amil are: first, the lack of education to the mosque community about zakat regulations; second, the lack of socialization of zakat regulations; and third, the narration of the Islamic State has not yet been completed.Keywords: Implementation, Zakat Regulation, Amil, North Medan Mosque.